Performance analyses of minimising emergency message collisions and maximising network throughput in IEEE 802.11p VANET network. (2015) - Chang, BenJye; Liang, YingHsin; Lai, JiunTing
IEEE 802.11p is proposed as the VANET wireless media access control (MAC) interface for the transmissions of emergency messages in V2V and V2I Communications. However, in a high mobility vehicular adhoc network (VANET), quality of service (QoS) of both the emergency message (EM) and handoff transmissions suffer from high collision probability of the contentionbased media access mechanism and high interference exhibiting near the celledge that encodes a low coding rate of the adaptive modulation and coding (AMC) scheme. Thus, this paper proposes an efficient MAC for IEEE 802.11p to solve above critical issues, in which the approach consists of three main mechanisms to dynamically determine contention window (CW) based on the sigmoid function. Numerical results demonstrate that the analysis results are close to the simulation results, and thus justify the correctness of the mathematical analytical model. In addition, the proposed approach outperforms the compared approaches (including the IEEE 802.11p std.) in EM transmission delay, collision probability, throughput and MAC frame dropping probability.